Calcium carbonate particles loaded with triethanolamine and polyethylenimine for enhanced corrosion protection of epoxy coated steel. (1st May 2020) - Raj, Roma; Morozov, Y.; Calado, L.M.; Taryba, M.G.; Kahraman, R.; Shakoor, R.A.; Montemor, M.F.
Graphical abstract: Highlights: CaCO3 microparticles were loaded with triethanolamine and polyethylenimine as corrosion inhibitors. The addition of the particles did not damage the barrier properties of epoxy coatings. Corrosion inhibition confirmed in artificial defects of the coatings modified with the inhibitor loaded CaCO3 microparticles Abstract: Calcium carbonate particles were synthesized and loaded with a mixture of two corrosion inhibitors, triethanolamine (TEA) and polyethylenimine (PEI). These particles can serve as pH-sensitive additives in epoxy coatings to provide "smarter" corrosion protection of carbon steel. Electrochemical impedance spectroscopy revealed that calcium carbonate particles loaded with the mixture of corrosion inhibitors improved corrosion resistance of coated panels and did not damage the barrier properties of the coating. Localized electrochemical studies of artificially damaged coatings on steel confirmed the corrosion inhibition effect.